Epidemic characteristics of foodborne disease outbreaks in Mengla County， Yunnan Province from 2017 to 2021 - LIU Chunmei; SUN Ling; BAI Jun; MAO Qi; ZHU Jing; HE Huizhi; CHENG Jinfang; NIU Xiaowen; YANG Xiaomin; YANG Hongyuan; LUO Huiping; HE Guomin (Shanghai yufang yixue, 2022)
ObjectiveTo analyze the epidemic characteristics of foodborne disease outbreaks in Mengla County， Yunnan Province， so as to provide basis for formulating corresponding prevention and control measures.MethodsThe data of foodborne disease outbreaks in Mengla County， Yunnan Province from 2017 to 2021 in the national "foodborne disease outbreak monitoring system" were collected. The time， population， region， place， pathogenic factors and inducing links of the events were statistically analyzed.ResultsFrom 2017 to 2021， a total of 68 incidents were reported， including 526 cases and 5 deaths. The total incidence rate was 23.40% and the case fatality rate was 0.95%. The peak period was from May to July， with the largest number of reported events in July. The reporting areas were mainly Mengla Town （35.29%）， Guanlei Town （11.76%） and Mengpeng Town （10.29%）. The main place of the incident was family （76.47%）. The main pathogenic factors were plant toxins （79.41%）， mainly through the ingestion of wild mushrooms （68.52%）， improper processing of green beans （12.96%） and aconitum （9.26%）.ConclusionAccording to the epidemiological characteristics of Mengla County， we should focus on the public education of health knowledge in key areas and places， especially on the identification of wild mushrooms， to prevent accidental eating. At the same time， we should strengthen the monitoring and risk assessment of foodborne diseases， find potential risks as soon as possible， issue early warning and forecast in time， and constantly improve the clinical treatment ability of poisoned patients.